1986
DOI: 10.1149/1.2108402
|View full text |Cite
|
Sign up to set email alerts
|

The Plasma Etching of Polysilicon with  CF 3Cl / Argon Discharges: III . Modeling of Etching Rate and Directionality

Abstract: P ~s energ.y scaling parameter based on predicted mean 1on energy scaling parameter, P/Po ion-neutral scattering cross section (cm 2) time-averaged sheath electric field (V/cm) [Additional symbols listed in Ref. (1)]ABSTRACT Three kinetic models, based on experimentally measured and theoretically estimated plasma properties, are developed to describe heavily P-doped polysilicon etching in CF3C1 (Freon | 13) RF discharges. The models include both chemical and ion-assisted processes, and, therefore, predict etch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 11 publications
0
22
0
Order By: Relevance
“…The average etching rate is defined as the ratio of the total depth, h, divided by the etch time (30 min). 25 The etching rate of silicon has three components: physical sputtering, spontaneous thermal etching, and ion-enhanced chemical reaction; the largest component being the ion-enhanced part. 6 and 7 were taken for trenches of nominal width, 64 m. The adjusted R 2 of the quadratic model for this response is 0.85 indicating that the fit is reasonably good.…”
Section: Resultsmentioning
confidence: 99%
“…The average etching rate is defined as the ratio of the total depth, h, divided by the etch time (30 min). 25 The etching rate of silicon has three components: physical sputtering, spontaneous thermal etching, and ion-enhanced chemical reaction; the largest component being the ion-enhanced part. 6 and 7 were taken for trenches of nominal width, 64 m. The adjusted R 2 of the quadratic model for this response is 0.85 indicating that the fit is reasonably good.…”
Section: Resultsmentioning
confidence: 99%
“…As the reaction rate is the number of Si atoms reacted per area and time, the rate constant is proportional to the product of the number density and the refreshing frequency of the activators, i.e., the incident flux of ions, ⌫ i . 8,[26][27][28] According to the collision cascade theory, 29 ions with high kinetic energy transfer their momentum to the surface species more effectively than ions with low energy.…”
Section: Resultsmentioning
confidence: 99%
“…Two etchers, a research etcher and a commercial etcher, were used in the current study. The main etcher used in this work was a parallel-plate single-wafer research etcher, which has been previously described (12,13) and is shown in Fig. 1.…”
Section: Methodsmentioning
confidence: 99%